Integration of Information for Environmental Security - Coskun, H. Gonca; Cigizoglu, H. Kerem; Maktav, M. Derya; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
In case of security threats there is a need for temporal access to complete, updated, reliable information, in a dedicated form, is an essential prerequisite to effectively counter security threats. Currently the necessary information exists in a multitude of forms and formats geographically and physically scattered over different countries, institutes and organisations, and are subject to widely different data policies and management schemes. Moreover, there is no complete and updated overview of the existing information, e.g. in the form of a metadata catalogue. As a result, integration of this information in case of emergencies has proven to be extremely difficult, if not impossible. Although in some cases, interesting and impressive "demonstrations" have been shown of the possibilities of the integration of information, for a number of reasons these have reached the "operational" stage.
Environmental Security -- An Integrated Approach For Environmental Security in the NATO Countries Based on Remote Sensing and GIS Technologies -- Geospatial Integration And Fusion Techniques For Environmental Monitoring And Security -- Integrated Use Of Multispectral Satellite And Airborne Sensors As A Tool For Detecting Biological Hot Spots And Monitor Of Aquatic Environment Security -- Data Policy And Management Issues For Integration Of Information: The Gmes Projects And Plans -- The Importance Of Itu-Cscrs For Natural Disaster Monitoring: A Case Study - Flooding In The Maritsa River -- Information Products to Study Environmental Threats and Dangerous Phenomena in the Black, Azov and Caspian Seas -- Gis And Models For Environmental Health Action Plans -- Information Security, Integration of Information -- Artificial Neural Networks In Water Resources -- Application Of Space Technology In Support Of Security And Safety Of Critical Infrastructure -- Online Information As An Important Source For Environmental Impact Studies -- The Use Of Numerical Simulation For Oil Spill Contingency Plan -- Monitoring Microcatchment By Using Satellite Imagery: Kiziloz Sample -- Emergency Warnings With Short Message Service -- Sustainable Development In Ukraine: Problem,New Vision, Solution -- The Role Of Space Assets In Providing For Public Security -- Role Of Geospatial Information And Geospatial Information Application Software Systems For Security -- Disaster Forecasting and Prevention -- Spatial Data Infrastructures For Emergency Services And Security Management -- Forest Fires And Remote Sensing -- Natural And Environmental Risks In Marine And Coastal Areas -- Integrated Monitoring System For Seismic Risk Assessment In Vrancea Area -- Forests And Natural Disasters -- The Role Of Remote Sensing And Gis For Security -- Technological Risk Assessment And Management:Can We Integrate Terrorist Attacks? -- Environmental Impact Of Lng Terminals In The Gulf Of Trieste (Northern Adriatic) -- Disaster Management Education And Policies In Turkey -- Water Resources Management -- Integrated Information Base For Sustainable Water Resources Management -- Coastal Zone Management/Coastal Information System -- Wastewater Management In Istanbul -- Ship'S Ballast Water And Marine Pollution -- Specialized Multidisciplinary Information System As A Tool To Support Monitoring Of Marine Ecosystem -- Management Of Water Supply Systems Of Metropoles: Istanbul Example.
Keywords: REMOTE SENSING; GEOGRAPHICAL INFORMATION SYSTEMS; ENVIRONMENTAL MANAGEMENT; ENVIRONMENTAL TOXICOLOGY; ENVIRONMENTAL POLLUTION; GEOSCIENCES; REMOTE SENSING/PHOTOGRAMMETRY.; ECOTOXICOLOGY; GEOGRAPHICAL INFORMATION SYSTEMS/CARTOGRAPHY.; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION; ENVIRONMENTAL MANAGEMENT